Fragmentation of multiply ionized biomolecules induced by MeV heavy ions. (July 2015) - Yoshida, S O; Majima, T; Asai, T; Matsubara, M; Tsuchida, H; Itoh, A
Synopsis: Collision-induced ionization and fragmentation of gas-phase adenine molecules (C5 N5 H5 ) have been investigated for single electron capture collisions of 1.2 MeV C 2+ ions. Coincidence measurements between the number of ejected electrons and the time-of-flight of fragment ions allows us to determine charge states of intermediate parent ions r . Highly charged parent ions are observed up to r ∼ 6 and the production of lighter fragment ions becomes predominant with increasing r . We found that kinetic energies of H + are significantly larger than those of other fragment ions and become nearly equivalent irrespective of r for r > 1.